Factors associated with adherence to anemia treatment among children under five years of age at Centro de Salud San Pedro, Ayacucho, 2021 - Choque Medrano, Edith (2025)
Objective: To determine the adherence to anemia treatment and the factors associated with it among children under five years of age at Centro de Salud San Pedro, Ayacucho, in 2021. Materials and methods: A quantitative, analytical, observational and cross-sectional study was conducted. The study population consisted of 138 mothers of children under five years of age diagnosed with anemia. Data were collected using two instruments: the Associated Factors and Adherence to Anemia Treatment Questionnaire and the Morisky Green Levine Medication Assessment Questionnaire, which measures adherence to treatment. Associations were assessed using the chi-square test, and a multivariate logistic regression analysis was performed. Statistical significance was set at p < 0.05 with a 95 % confidence interval (CI). All analyses were carried out using IBM SPSS Statistics 26. Results: Adherence to anemia treatment was observed in 26.8 % of the participants. Six factors were found to be associated with adherence. Five of them increased adherence: having the illness for more than six months, which raised adherence by 3.9 times (adjusted odds ratio [aOR]: 3.959, 95 % CI: 1.367-11.469); maternal age < 35 years, which elevated adherence by 10 % (aOR: 1.124, 95 % CI: 1.043-1.211); belonging to a nuclear family, which doubled adherence (aOR: 2.010, 95 % CI: 1.161-3.480); having completed primary education, which improved adherence by 2.6 times (aOR: 2.650, 95 % CI: 1.205-5.824) and knowing that anemia can be cured with a diet rich in iron, which boosted adherence by 3.1 times (aOR: 3.153, 95 % CI: 1.144-8.685). However, being younger than two years of age reduced adherence by 27 % (aOR: 0.732, 95 % CI: 0.546-0.981). Conclusions: Adherence to anemia treatment among children under five years of age was low, with six associated factors identified: five that increased adherence and one that decreased it. Targeting modifiable factors, such as educational level and knowledge about anemia treatment, is recommended.